2005
DOI: 10.1007/11596448_11
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal FeedForward Self-organizing Maps

Abstract: Abstract. We introduce a novel system of interconnected SelfOrganizing Maps that can be used to build feedforward and recurrent networks of maps. Prime application of interconnected maps is in modelling systems that operate with multimodal data as for example in visual and auditory cortices and multimodal association areas in cortex. A detailed example of animal categorization in which the feedworward network of self-organizing maps is employed is presented. In the example we operate with 18-dimensional data p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…The feedback from the bimodal area to the auditory area should thus cause activity there even in the absence of auditory stimuli, provided a visual stimulus is present. In later modeling work (Gustafsson, Jantvik, & Papliński, 2007), an extended artificial neural network architecture with more versatile modules than those used previously (Papliński & Gustafsson, 2005Chou et al, 2007) was shown to replicate this property also, while still replicating the properties of earlier versions of the architecture.…”
Section: Introductionmentioning
confidence: 92%
“…The feedback from the bimodal area to the auditory area should thus cause activity there even in the absence of auditory stimuli, provided a visual stimulus is present. In later modeling work (Gustafsson, Jantvik, & Papliński, 2007), an extended artificial neural network architecture with more versatile modules than those used previously (Papliński & Gustafsson, 2005Chou et al, 2007) was shown to replicate this property also, while still replicating the properties of earlier versions of the architecture.…”
Section: Introductionmentioning
confidence: 92%
“…This association can then be used to influence the selforganization of monomodal maps [46]. The use of self-organizing maps to learn multimodal associations has been studied by several authors [88,68,35,71,84,40]. If these architectures are good at learning crossmodal associations, they suffer from the curse of dimensionality: projecting high dimensional data to two or three dimensions by preserving local topology (on which usually rely crossmodal associations) is difficult.…”
Section: Multimodal Fusionmentioning
confidence: 99%
“…Kohonen Self-Organizing Maps (SOMs) are well-recognized and intensively researched tools for mapping multidimensional stimuli onto a low dimensionality (typically 2) neuronal lattice, for an introduction and a review, see [26]. In this paper we will employ a network of interconnected SOMs, referred to as Multimodal Self-Organizing Networks (MuSONs), see [23,24]. We consider first a feedforward Multimodal Self-Organizing Network (Mu-SON) as presented in the left part of Figure 1.…”
Section: The Multimodal Self-organizing Networkmentioning
confidence: 99%
“…Three-dimensional outputs from these maps, y lt and y ph , are combined together to form a six-dimensional stimulus for the higher-level bimodal map, SOM bm . The learning process takes place concurrently for each SOM, according to the well-known Kohonen learning law, see [23,24] The position of the winner can be determined from the network (map) postsynaptic activity, d(k) = W · x(k). As an example, in Figure 2, we show the post-synaptic activity of a trained bimodal map when the visual letter stimulus x lt (k) and the auditory phoneme stimulus x ph (k) representing letter/phonemeö is presented.…”
Section: The Multimodal Self-organizing Networkmentioning
confidence: 99%
See 1 more Smart Citation